Thinking Skills and the Learning of Primary History: Thinking Historically through Stories. Issue 2 (1st July 2004) - Vass, Peter
This paper derived from a piece of research undertaken in an Oxfordshire primary school in the summer of 2002. Part 1 introduces the question of thinking skills. Part 2 examines how thinking skills might enhance children's learning of history via a case study of a project in an Oxfordshire primary school. The project's focus was on the potential of narrative, and in particular counterfactuals, in this respect.